Hubungan Kadar Vitamin D dengan Kasus Preeklamsia pada Kehamilan - Aryn Shadira Anesti; Adrian Setiawan; Elli Arsita (Jurnal MedScientiae, 2023)
Preeclampsia is a pregnancy disorder with serious complications marked by hypertension and proteinuria finding. Vitamin D deficiency is one of the risk factors of preeclampsia with a prevalence of 18-84% worldwide. The objective of this literature review is to determine the relationship between vitamin D levels in with occurrence of preeclampsia in pregnancy. The database that were used was PubMed with “Preeclampsia”, “Level'', and “Vitamin D” as keywords. Inclusion and exclusion criteria were applied in choosing journals that are used. The results of this paper indicates that patient with 25(OH)D serum levels below 30 ng/mL are more at risk of experiencing preeclampsia. This literature review indicates that there is a correlation between vitamin D levels and preeclampsia. Vitamin D supplementation is recommended as one or other ways to prevent preeclampsia. Nonetheless, is no research proving that consuming vitamin D supplement during pregnancy regularly and consistently can significantly increase 25(OH)D serum levels status. The optimal levels of vitamin D serum before pregnancy can minimalize the risk of preeclampsia. Further research is needed to inspect the dose of vitamin D supplementation that is effective to reduce preeclampsia incidence.